THE IMPACT OF MERGERS AND ACQUISITIONS ON EARNING MANAGEMENT PRACTICES AND FINANCIAL PERFORMANCE - Dewi Sarifah Tullah; Ramunah Fatmawati Tullah (Riset: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2023)
This study aims to determine whether there are differences between earning management and financial performance during mergers and acquisitions (M&A). Purposive sampling was used to collect data from the Indonesia Stock Exchange (IDX) according to criteria for businesses that completed M&A projects in 2017 and that were publicly traded from 2012 to 2020. The Wilcoxon signed rank test was used to test the hypothesis. The results of the study show that earnings management practices are different after M&A is done with income-increasing patterns. The financial performance of return on assets (ROA) proves that there are differences that cause these activities to decline. But even while these ratios are suffering from a decline, impact M&A does not produce appreciable differences in the current ratio (CR), debt to equity ratio (DER), total asset turnover (TATO), and earnings per share (EPS). Research suggests that businesses exercise greater caution when developing their business plans prior to implementing M&A, and that investors be more picky when allocating capital to businesses that are implementing M&A because not all M&A activities will result in positive outcomes.